Moderasi Persepsi Kegunaan dan Kemudahan Pembelajaran terhadap Pengaruh Minat Belajar pada Tingkat Pemahaman Akuntansi - Agung Kresnandra, Anak Agung Ngurah; Anggara, I Wayan Gde Wahyu Purna (E-Jurnal Akuntansi, 2022)
This study aims to determine the moderating ability of the perceived usefulness and convenience of online learning media at OASE Udayana on the influence of accounting students' learning interest on their level of accounting understanding. The primary data of this research is the distribution of questionnaires using purposive sampling method. The collected data is first tested for the fulfillment of the classical assumption requirements, then analyzed using the technique of moderated regression analysis (MRA). The results of this study are that interest in learning statistically affects the level of accounting understanding, perceptions of the usefulness of online learning media are not able to strengthen or weaken the influence of interest in learning on the level of accounting understanding and perceived ease of moderating the effect of interest in learning on the level of accounting understanding. Keywords: Learning Interests; Perceptions of Usefulness; Perceptions of Ease; Level of Accounting Understanding.